2019
DOI: 10.1021/jacs.9b02893
|View full text |Cite
|
Sign up to set email alerts
|

Energy Decomposition Analyses Reveal the Origins of Catalyst and Nucleophile Effects on Regioselectivity in Nucleopalladation of Alkenes

Abstract: Nucleopalladation is one of the most common mechanisms for Pd-catalyzed hydro- and oxidative functionalization of alkenes. Due to the electronic bias of the π-alkene-palladium complexes, nucleopalladations with terminal aliphatic alkenes typically deliver the nucleophile to the more substituted sp2 carbon to form the Markovnikov-selective products. The selective formation of the anti-Markovnikov nucleopalladation products requires the inherent electronic effects to be overridden, which is still a significant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 74 publications
(77 reference statements)
2
35
0
Order By: Relevance
“…In addition, there is also a weak H-bonding interaction (H 1 –O 1 distance of 2.563 and 2.633 Å, in TS-6p and TS-6d , respectively, Figure ) between the Pd-coordinated Ph and O-center of the OR-substituent. To provide additional support for the analysis presented above and identify other factors that possibly impact the interaction between the sub and ligand fragments in TS-6p and TS-6d , we also performed natural energy decomposition analysis (NEDA) calculations . These studies (see the Supporting Information for more details) have identified that weak interactions (e.g., van der Waals, dipole–dipole, and dipole–(induced dipole)), combined under the electrical interaction (EL) term, do not contribute significantly to the calculated energy difference between TS-6p and TS-6d , and a charge transfer (CT) interaction between the ligand and sub fragments contributes significantly to the calculated total electronic energies of TS-6p and TS-6d : it is 8.1 kcal/mol larger in TS-6p than in TS-6d . …”
Section: Resultssupporting
confidence: 94%
“…In addition, there is also a weak H-bonding interaction (H 1 –O 1 distance of 2.563 and 2.633 Å, in TS-6p and TS-6d , respectively, Figure ) between the Pd-coordinated Ph and O-center of the OR-substituent. To provide additional support for the analysis presented above and identify other factors that possibly impact the interaction between the sub and ligand fragments in TS-6p and TS-6d , we also performed natural energy decomposition analysis (NEDA) calculations . These studies (see the Supporting Information for more details) have identified that weak interactions (e.g., van der Waals, dipole–dipole, and dipole–(induced dipole)), combined under the electrical interaction (EL) term, do not contribute significantly to the calculated energy difference between TS-6p and TS-6d , and a charge transfer (CT) interaction between the ligand and sub fragments contributes significantly to the calculated total electronic energies of TS-6p and TS-6d : it is 8.1 kcal/mol larger in TS-6p than in TS-6d . …”
Section: Resultssupporting
confidence: 94%
“…Due to the relatively rigid conformation of (R)-SPINOL-C1 catalyst, stacking-type model is favored for the TSs of proton transfer step to fit the cavity of catalyst with certain entropy loss, leading to S-axial chirality configuration. That is consistent with less steric repulsion between catalyst and substrate in the stackingtype model, which is the dominant effect by Energy Decomposition Analysis (EDA) calculations 68 as shown in Fig. 5b.…”
Section: Resultssupporting
confidence: 81%
“…The α,β‐unsaturated aldehyde 3 a was formed via the dehydrogenation of 2 a catalyzed by palladium in the presence of BQ as a hydrogen acceptor (vide infra) . Some bulky secondary and tertiary alcohols were examined as the reaction solvent because steric hindrance was expected to control the regioselectivity of the reaction to preferentially form the anti‐Markovnikov product . t ‐BuOH was found to be the optimal solvent (Table S2).…”
Section: Resultsmentioning
confidence: 99%